A Study of Frequency of Low Backache in Pregnant Women - Shah, Syed Fahd; Mumtaz, Syed Naveed; Kayani, Bushra Afzal; Shah, Syed Hussain; Khan, M. Wasi Ullah; Khan, Abdul Qadir (Pakistan Armed Forces Medical Journal, 2022)
Objective: To find the frequency of backache in our pregnant women and factors increasing the risk of low backache in pregnancy.Study Design: Prospective longitudinal study.Place and Duration of Study: Department of Gynecology & Obstetrics, Avicenna Medical College, Lahore Pakistan, from Jan 2018 to Dec 2019.Methodology: We included 247 consecutive women between 18 and 45 years of age and between 16 and 35 weeks of a single pregnancy. These were evaluated for low backache. Women with comorbid conditions and multiple fetuses who needed elective caesarian sections were excluded.Results: Mean age of the pregnant women in our study was 27 ± 3.7 years, with an age range of 18 to 45 years. 197 (80.1%) complained about low back pain during their pregnancy, and 75 (30.3%) had a previous history of back pain when not pregnant. Back pain was present in 47 (19.02%) 6 months postpartum. The risk factors present were higher weight gain in 75 (30 %), age >35 years in 62 (25 %), low haemoglobin 38 (15%) and poor socio-economic condition 25 (10.1%).Conclusion: Low back pain is common in pregnancy and is a less addressed issue of pregnant women. Many factors responsible for low backache in pregnant women were identified. Analgesics and increased physical activity are the main treatment and prevention options.